Conformation and EPR characterization of rigid, 310‐helical peptides with TOAC spin labels: Models for short distances. Issue 3 (May 2014) - Shabestari, Maryam Hashemi; van Son, Martin; Moretto, Alessandro; Crisma, Marco; Toniolo, Claudio; Huber, Martina
<x xml:space="preserve">Abstract</x> For 3D‐structure determination in biophysical systems EPR is rapidly gaining ground. Proteins labeled specifically with two nitroxide spin labels can be prepared, and several EPR methods are available for distance determination, which makes it possible to determine distance constraints. However, such methods require frozen solutions, potentially causing non‐physiological states of the sample. Here, we target spin– spin interaction in liquid solution at room temperature using rigid model compounds. A series of 310‐helical peptides, based on α‐aminoisobutyric acid (Aib), is synthesized with pairs of spin labels separated by three, four, and five amino acids. To avoid flexibility, the noncoded nitroxyl‐containing α‐amino acid TOAC that is rigidly connected with the peptide backbone, is used. The EPR spectra of the peptides show a decreasing amount of coupling between the two spin labels within this series. We suggest through‐bond interaction as the dominating mechanism for exchange interaction (J) and find a stronger J‐coupling than in the corresponding Ala‐based TOAC‐peptides investigated previously (Hanson, et al., J Am Chem Soc 1996, 118, 7618–7625). We speculate that stronger coupling in Aib‐ vs Ala‐ peptides is due to intrinsically stronger through‐bond interaction in the Aib‐based peptides. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 244–251, 2014.